2022
DOI: 10.3390/ma15207325
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of LiCo1-1.5xYxPO4@C Cathode Material for High-Energy Lithium-ion Batteries

Abstract: Intrinsically low ion conductivity and unstable cathode electrolyte interface are two important factors affecting the performances of LiCoPO4 cathode material. Herein, a series of LiCo1-1.5xYxPO4@C (x = 0, 0.01, 0.02, 0.03) cathode material is synthesized by a one-step method. The influence of Y substitution amount is optimized and discussed. The structure and morphology of LiCo1-1.5xYxPO4@C cathode material does not lead to obvious changes with Y substitution. However, the Li/Co antisite defect is minimized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Generally, a LiNiPO4 cathode exhibits a flat plateau at approximately 5 V, corresponding to the Ni 3+ /Ni 2+ redox couple [58]. The LNCP cathode shows a discharge voltage plateau at about 4.8 V, which is slightly lower considering the expected Ni 3+ /Ni 2+ redox couple but is in good agreement with previous publications for the Co 3+ /Co 2+ redox couple in LiCoPO4 [11,13]. When an LNCP cathode is combined with an LTO anode, this full cell displays a discharge plateau at 3.12 V in the voltage profile during the galvanostatic cycling test (Figure 4d).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Generally, a LiNiPO4 cathode exhibits a flat plateau at approximately 5 V, corresponding to the Ni 3+ /Ni 2+ redox couple [58]. The LNCP cathode shows a discharge voltage plateau at about 4.8 V, which is slightly lower considering the expected Ni 3+ /Ni 2+ redox couple but is in good agreement with previous publications for the Co 3+ /Co 2+ redox couple in LiCoPO4 [11,13]. When an LNCP cathode is combined with an LTO anode, this full cell displays a discharge plateau at 3.12 V in the voltage profile during the galvanostatic cycling test (Figure 4d).…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, the sluggish kinetics of the electronic and lithium-ion transport for these cathodes pose a major constraint to their development. Numerous modifications have been adapted to improve the Li extraction/insertion kinetics and electronic conductivity, including morphology control [11,12], metal ion doping [13], metal oxide coating [14][15][16], and carbon coating [17,18]. Manickam Minakshi et al have conducted several studies on olivine cathodes [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As such, there is a need for reliable cobalt free cathodes, and layered lithium rich nickel manganese oxides (LLRNMO), specifically those within the compositional range of Li[Ni x Li (1/3-2x/3) Mn (2/3−x/3) ]O 2 (x <.50), have demonstrated high (>200 mAh g −1 ) specific capacities, and high functional voltage windows (2.0-4.8 V), making them a promising family of cobalt free cathode materials. [4][5][6][7] LLRNMO materials have a large body of literature dedicated to their structure, and electrochemical behaviors. 4,5,[8][9][10] The main drawbacks of these materials are their low rate capabilities, and poor capacity retention caused by structural instability wherein the materials experience oxygen losses, and the migration of transition metal ions over the course of cycling.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,[8][9][10] The main drawbacks of these materials are their low rate capabilities, and poor capacity retention caused by structural instability wherein the materials experience oxygen losses, and the migration of transition metal ions over the course of cycling. [5][6][7][8][11][12][13] Several complex synthetic routes using scaffolds, dopants or surface modifications and coatings on LLRNMOs can help mitigate oxygen loss and thus serve to improve functionality. 6,[14][15][16][17][18][19][20][21] More recently it has been demonstrated that an O2-type oxygen structure can prevent undesirable irreversible transition metal ion migration, thereby greatly improving capacity retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation